Transforming the Golden-Age Nation State
XVI, 213 p.
Keywords: This collection examines the transformation of the modern Western state in an age of accelerated globalization. Arguing that the state experienced a 'golden age' in the 1960s and 1970s, the contributors explore how and why this configuration of the state is under pressure in the 21st century.